Meat Characteristics, Expression of Myosin Heavy Chain and Metabolism-Related Genes in Thai Native Pigs - Chanporn Chaosap; Kamon Chaweewan; Kazeem D. Adeyemi; Netanong Phonkate; Ronachai Sitthigripong (Foods, 2024)
This study investigated the meat quality, expression of myosin heavy chain (MyHC) and metabolism-related genes, ribonucleotides and fatty acids in Longissimus thoracis of Thai native pigs (TNPs) from different geographical regions (GR). Forty-one 9–10-month-old castrated TNPs (BW 60 kg), consisting of 18, 11 and 12 pigs from Northern (NT), Southern (ST) and Northeastern (NE) regions, respectively, were slaughtered. GR did not affect (p > 0.05) the expression of MyHC, phosphoglycerate mutase 1, cytosolic glycerol-3-phosphate dehydrogenase, triosephosphate isomerase 1 and adipocyte fatty acid binding protein genes. The trend of MyHC was MyHC IIx > MyHC IIb > MyHC IIa > MyHC I. The NT loin had higher (p < 0.05) glycogen, C18:2n6, C20:4n6 and cooking loss, lower inosine, inosine monophosphate and hypoxanthine and a shorter sarcomere length than the ST and NE loins. The ST loin had a lower (p < 0.05) a* compared to other loins. Principal component analysis established significant relationships between the TNP and specific meat quality traits. This finding suggests that GR affected the meat quality, ribonucleotides and selected fatty acids in TNPs. These results provide relevant information that can be used to optimize the use of Thai native pork.